2009
DOI: 10.1093/jeg/lbp036
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, spillovers and university-industry collaboration: an extended knowledge production function approach

Abstract: This paper analyses the effect of knowledge spillovers from academic research on regional innovation. Spillovers are localized to the extent that the underlying mechanisms are geographically bounded. However, university-industry collaboration-as one of the carriers of knowledge spillovers-is not limited to the regional scale. Consequently, we expect spillovers to take place over longer distances. The effect of university-industry collaboration networks on knowledge spillovers is modelled using an extended know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
281
2
20

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(316 citation statements)
references
References 71 publications
13
281
2
20
Order By: Relevance
“…Econometric analysis of spatial autocorrelation phenomena is well diffused in the innovation literature, and use of alternative measures of technological, institutional, social and organizational neighbours has been discussed in depth (Torre and Gilly 2000;Boschma 2005;Cantner and Meder 2007;Boschma and Frenken 2009;Ponds et al 2007Ponds et al , 2010Marrocu et al 2013a). However, the innovative and explorative contribution of this paper consists of identifying an estimation method which considers the research object rather than the research network to compute an alternative measure of proximity.…”
Section: Knowledge Flow Network: Their Structure and Layoutmentioning
confidence: 99%
“…Econometric analysis of spatial autocorrelation phenomena is well diffused in the innovation literature, and use of alternative measures of technological, institutional, social and organizational neighbours has been discussed in depth (Torre and Gilly 2000;Boschma 2005;Cantner and Meder 2007;Boschma and Frenken 2009;Ponds et al 2007Ponds et al , 2010Marrocu et al 2013a). However, the innovative and explorative contribution of this paper consists of identifying an estimation method which considers the research object rather than the research network to compute an alternative measure of proximity.…”
Section: Knowledge Flow Network: Their Structure and Layoutmentioning
confidence: 99%
“…The analysis is based on the KPF (formalised by Griliches, 1979;and Jaffe, 1986) but adopts a place-based perspective, with Italian provinces (NUTS3 level) as units of observation. This specification of the KPF is customary in the literature on regional innovation (Audretsch, 2003;Audretsch and Feldman 1996;Crescenzi and Rodriguez-Pose, 2011;Crescenzi et al, 2007;Feldman, 1994;Fritsch, 2002;Moreno et al 2005a;O'hUallachain and Leslie, 2007;Ponds et al, 2010;Varga, 1998) and allows us to focus upon the territorial dynamics of innovation by taking account of both total social capital endowment and its bonding and bridging components as determinants of regional innovative performance. The Regional Knowledge Production Function takes the following form: inventions.…”
Section: Model Of Empirical Investigationmentioning
confidence: 99%
“…Innovation input-'Private R&D as a share of GDP' and the number of graduates over the total population are used as proxies for the key inputs of the 'standard' regional Knowledge Production Function (Crescenzi et al, 2007;Moreno et al, 2005b;O'hUallachain and Leslie, 2007;Ponds et al, 2010;Varga, 1998). On account of limited data availability our R&D measure is available only at regional level (NUTS 2) while the number of graduates is available for each province (NUTS3).…”
Section: Model Of Empirical Investigationmentioning
confidence: 99%
“…In verifying this argument, some recent empirical studies have clearly shown that firms tend to search for new cooperation actors or establish branches in similarly specialized clusters and/or metropolitan areas so as to obtain more unconscious knowledge spillover (Poon et al 2013;Boschma et al 2014;Gabe and Abel 2016). In addition, due to their importance for the availability of highly qualified labor (Ponds et al 2010;Huggins et al 2014), the presence of academic research institutes and universities is expected to influence the local actors' knowledge base and their innovation potential. Firms located in places with rich resource endowments are more likely to discover and utilize partners on different geographical scales (Wang and Lin 2013;Hewitt-dundas 2013).…”
Section: Regional Environmentmentioning
confidence: 94%